Consortia of Central American university libraries: REDSIID - Miranda Arguedas, Alice (2001)
In order to participate in the debate on consortiums that has been generated at present, this document presents a description of the experience of the Network of Integrated Systems of Documentary Information of the Universities members of the Central American Higher University Council REDSIID/CSUCA, which aims to be an academic consortium librarian. Structure of cooperation that could benefit the Central American region